IMPLEMENTATION OF THE VILLAGE SUSTAINABLE DEVELOPMENT GOALS (SDGS) PROGRAM IN REDUCING POVERTY THROUGH THE BLT-DD PROGRAM SUGIHWARAS VILLAGE, CANDI DISTRICT, SIDOARJO REGENCY - Mulisalsabilla, Shinta Ana; Rodiyah, Isnaini (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: Poverty is one of the biggest challenges faced by people around the world, including Indonesia. Although poverty rates have declined in recent years, millions of people still live below the poverty line. In this context, the implementation of the Sustainable Development Goals (SDGs) Program in Sugihwaras Village, Candi District, Sidoarjo Regency, is very relevant. This study aims to analyze how the Village Fund Direct Cash Assistance (BLT-DD) program can contribute to reducing poverty in villages. Method: The research method used is qualitative with a descriptive approach, which involves observation, interviews, and document collection. Results: The results of the study show that the BLT-DD program provides significant financial support for beneficiary families, especially in meeting their basic needs. In addition, this program also has the potential to encourage people to invest in small businesses, thereby improving overall welfare. However, the successful implementation of this program is influenced by several factors, including effective communication between the government and the community, adequate resource management, and a clear bureaucratic structure. A positive attitude from all parties involved is also key in achieving poverty alleviation goals. Novelty: The study adopts a theoretical approach put forward by George C. Edwards III, which details four important components in policy implementation, namely communication, resources, bureaucratic structure, and disposition. This approach is innovative because it not only focuses on financial impact analysis, but also explores the interactions and synergies between non-financial factors that significantly determine the success of the BLT-DD program.